A direct and soft synthesis of biomimetic imprints in a stationary phase via sol-gel polymerization of silylated amino acids for selective separation of proteins - Yoann Ladner; Margaux Clavié; Jérémie Gouyon; Tristan Corbalan; Raquel Gutiérrez-Climente; Giang Ngo; Pascal Etienne; Philippe Rondard; Pierre-André Lafon; Pascal Dumy; Pierre Martineau; Martine Pugnière; et al. (Analytica Chimica Acta, 2026)

Disentangling Environmental and Within‐Host Drivers of Parasite Dynamics in Natural Populations - Antoine Perrin; Heinz Richner; Molly Baur; Olivier Glaizot; Philippe Christe (Molecular Ecology, 2026)
Understanding how parasite communities assemble and persist in the wild requires integrating both spatial and temporal dynamics, especially in systems involving multiple co‐circulating lineages. Using a unique 28‐year dataset of individually monitored great tits ( Parus major ) from five sites in western Switzerland, we investigated the eco‐evolutionary dynamics of haemosporidian parasites ( Plasmodium and Haemoproteus ). We examined (i) spatial and temporal variation in parasite prevalence and lineage composition, (ii) differences in host recovery across lineages, and (iii) within‐host transitions and evidence of competitive interactions. We found significant spatial patterns of prevalence and lineage dominance, not explained by a simple urban–rural gradient, with environmental filtering likely driving local parasite assemblages. While prevalence fluctuated across years, lineage composition remained temporally stable, suggesting long‐term coexistence shaped by site‐specific conditions. Recovery rates, based on whether birds cleared their infection between recaptures, varied across parasite lineages, suggesting lineage‐specific differences in infection persistence. In addition, Plasmodium homonucleophilum (SW2 lineage) frequently replaced other Plasmodium lineages within hosts but was never itself replaced, consistent with a pattern of competitive exclusion. Our results highlight the importance of spatial heterogeneity, local interactions, and lineage‐specific traits in shaping parasite communities over space and time. This study underscores the value of long‐term, individual‐based monitoring to understand natural parasite dynamics and the processes driving multi‐lineage coexistence.

Citizen science approach for genetic species identification in a local French seafood speciality - Babett Günther; Nicolas Bierne; Philippe Borsa; Cécile Perrin; Olivier Ripoll; Fanny Darbois; Sophie Arnaud-Haond (International Journal of Gastronomy and Food Science, 2024)

Worldwide impacts of landscape anthropization on mosquito abundance and diversity: A meta‐analysis - Antoine Perrin; Olivier Glaizot; Philippe Christe (Global Change Biology, 2022)
In recent decades, the emergence and resurgence of vector‐borne diseases have been well documented worldwide, especially in tropical regions where protection and defense tools for human populations are still very limited. In this context, the dynamics of pathogens are influenced by landscape anthropization (i.e., urbanization, deforestation, and agricultural development), and one of the mechanisms through which this occurs is a change in the abundance and/or diversity of the vectors. An increasing number of empirical studies have described heterogeneous effects of landscape anthropization on vector communities; therefore, it is difficult to have an overall picture of these effects on a global scale. Here, we performed a meta‐analysis to quantify the impacts of landscape anthropization on a global scale on the presence/abundance and diversity of mosquitoes, the most important arthropods affecting human health. We obtained 338 effect sizes on 132 mosquito species, compiled from 107 studies in 52 countries that covered almost every part of the world. The results of the meta‐analysis showed an overall decline of mosquito presence/abundance and diversity in response to urbanization, deforestation, and agricultural development, except for a few mosquito species that have been able to exploit landscape anthropization well. Our results highlighted that these few favored mosquito species are those of global concern. They, thus, provide a better understanding of the overall effect of landscape anthropization on vector communities and, more importantly, suggest a greater risk of emergence and transmission of vector‐borne diseases in human‐modified landscapes.

Comparison of high-frequency intensive balneotherapy with low-frequency balneotherapy combined with land-based exercise on postural control in symptomatic knee osteoarthritis: a randomized clinical trial - Laetitia Peultier-Celli; Alexis Lion; Isabelle Chary-Valckenaere; Damien Loeuille; Zheng Zhang; Anne-Christine Rat; René Gueguen; Jean Paysant; Philippe P. Perrin (International Journal of Biometeorology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Phylogeography of a cryptic speciation continuum in Eurasian spadefoot toads ( Pelobates ) - Christophe Dufresnes; Ilias Strachinis; Nataliia Suriadna; Galyna Mykytynets; Dan Cogălniceanu; Paul Székely; Tanja Vukov; Jan W. Arntzen; Ben Wielstra; Petros Lymberakis; Eli Geffen; Sarig Gafny; et al. (Molecular Ecology, 2019)
Cryptic phylogeographic diversifications provide unique models to examine the role of phylogenetic divergence on the evolution of reproductive isolation, without extrinsic factors such as ecological and behavioural differentiation. Yet, to date very few comparative studies have been attempted within such radiations. Here, we characterize a new speciation continuum in a group of widespread Eurasian amphibians, the Pelobates spadefoot toads, by conducting multilocus (restriction site associated DNA sequencing and mitochondrial DNA) phylogenetic, phylogeographic and hybrid zone analyses. Within the P. syriacus complex, we discovered species‐level cryptic divergences (>5 million years ago [My]) between populations distributed in the Near‐East (hereafter P. syriacus sensu stricto [ s.s .]) and southeastern Europe (hereafter P. balcanicus ), each featuring deep intraspecific lineages. Altogether, we could scale hybridizability to divergence time along six different stages, spanning from sympatry without gene flow ( P. fuscus and P. balcanicus , >10 My), parapatry with highly restricted hybridization ( P. balcanicus and P. syriacus s.s ., >5 My), narrow hybrid zones (~15 km) consistent with partial reproductive isolation ( P. fuscus and P. vespertinus , ~3 My), to extensive admixture between Pleistocene and refugial lineages (≤2 My). This full spectrum empirically supports a gradual build up of reproductive barriers through time, reversible up until a threshold that we estimate at ~3 My. Hence, cryptic phylogeographic lineages may fade away or become reproductively isolated species simply depending on the time they persist in allopatry, and without definite ecomorphological divergence.

Influence of meteorological elements on balance control and pain in patients with symptomatic knee osteoarthritis - Laetitia Peultier; Alexis Lion; Isabelle Chary-Valckenaere; Damien Loeuille; Zheng Zhang; Anne-Christine Rat; René Gueguen; Jean Paysant; Philippe P. Perrin (International Journal of Biometeorology, 2017)

Mapping Fifteen Trace Elements in Human Seminal Plasma and Sperm DNA - Sazan Ali; Florence Chaspoul; Loundou Anderson; David Bergé-Lefranc; Vincent Achard; Jeanne Perrin; Philippe Gallice; Marie Guichaoua (Biological Trace Element Research, 2017)

Visuo-oculomotor skills related to the visual demands of sporting environments - Hadrien Ceyte; Alexis Lion; Sébastien Caudron; Philippe Perrin; Gérome C. Gauchard (Experimental Brain Research, 2017)

Does calculating impair postural stabilization allowed by visual cues? - Hadrien Ceyte; Alexis Lion; Sébastien Caudron; Badreddine Kriem; Philippe P. Perrin; Gérome C. Gauchard (Experimental Brain Research, 2014)

Effect of Chronic and Subchronic Organic Solvents Exposure on Balance Control of Workers in Plant Manufacturing Adhesive Materials - Guillaume Herpin; Imed Gargouri; Gérome C. Gauchard; Catherine Nisse; Moncef Khadhraoui; Boubaker Elleuch; Denis Zmirou-Navier; Philippe P. Perrin (Neurotoxicity Research, 2009)

Impaired neuromotor functions in hospital laboratory workers exposed to low levels of organic solvents - Guillaume Herpin; Gérome C. Gauchard; Alexandre Vouriot; Bernard Hannhart; Alain Barot; Jean-Marie Mur; Denis Zmirou-Navier; Philippe P. Perrin (Neurotoxicity Research, 2008)

Contributions of occupational hazards and human factors in occupational injuries and their associations with job, age and type of injuries in railway workers - Nearkasen Chau; Gerome C. Gauchard; Dominique Dehaene; Lahoucine Benamghar; Christian Touron; Philippe P. Perrin; Jean-Marie Mur (International Archives of Occupational and Environmental Health, 2007)

Long-term exposure to solvents impairs vigilance and postural control in serigraphy workers - Alexandre Vouriot; Bernard Hannhart; Gérome C. Gauchard; Alain Barot; Torbjorn Ledin; Jean-Marie Mur; Philippe P. Perrin (International Archives of Occupational and Environmental Health, 2005)

Relationships of job, age, and life conditions with the causes and severity of occupational injuries in construction workers - Nearkasen Chau; Grome C. Gauchard; Christian Siegfried; Lahoucine Benamghar; Jean-Louis Dangelzer; Martine Franais; Rgis Jacquin; Alain Sourdot; Philippe P. Perrin; Jean-Marie Mur (International Archives of Occupational and Environmental Health, 2004)

Endogenous cytokinins as biochemical markers of rubber-tree (Hevea brasiliensis) clone rejuvenation - Yolande Perrin; Patrick Doumas; Ludovic Lardets; Marc-Philippe Carrons (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)